The Parametrized Newton-Secant Method for Finding an Eigenpair of the Symmetric Quadratic Eigenvalue Problem in an Interval - Datta, Karabi; Hong, Yoopyo; Thapa, Mohan (Nepal Journal of Mathematical Sciences, 2021)
Available with pdf